TRANSFORMATION OF EMOTIONS INTO CREATIVITY AS A WAY OF SOLVING PROBLEMS - Shmyreva, Olga (Revista Inclusiones, 2020)
The relevance of this research stems from the ambiguous influence of emotions on how problems are solved by a person and its outcome. The article aims to consider how emotions transform into creativity during solving problems and the specifics of this process. The survey method, the methods of comparison and grouping and interpretation of landscapes were used as the main methods to explore this problem. Subjective assessment and interpretation enabled to assess the attitude to the living space and allowed the author to reveal the dominant factors of time perspective. The article presents the findings of a survey of 90 teenagers aged 13-14 years old. Emotions play a particular role in constructing the time perspective which is a specific task of adolescence. Depending on the nature of emotional experiences, the person identifies himself with certain periods of time perspective. Emotional assessment of the world and emotional self-assessment turn out to be linked with factors of time perspective, namely, the content of temporal characteristics reflects the specifics of emotional attitude to oneself and the world. Emotional attitude promotes the construction of time perspective and develops a serious or "don't care" attitude to time. Discovering time for oneself and oneself in time passing allows a person to see himself in the future, build his own image in the time perspective; discovery of time expands the scope of the person's consciousness. Emotional attitude also facilitates self-knowing as it helps to build cause-effect relationships between images of oneself at different points of time perspective: the person not only projects his own expectations into the future, but also reflects on the past experience, begins to understand the motives of real choices, including the functions of self-knowing, planning, design, and self-control. The materials of this article can be useful for the development of the personality regarding its psychological and pedagogical aspects.